Empowerment through articulations between post-neoliberal politics and neoliberalism: value chain alliances in Bolivia - Córdoba, Diana M.; Jasen, Kees; González, Carolina (Informa UK Limited, 2017)
Development cooperation between the "New Left" governments in Latin America and the World Bank shows the paradoxical and complex nature of social transformation processes initiated by these governments. Using the case of Bolivia, we analyse how the government of Evo Morales seeks to realise its political goals while introducing elements of neoliberal governance prescribed by the World Bank through the Rural Alliances Project. Though full of contradictions, a neocollectivist practice emerges that succeeds in combining political empowerment of social movements with specific modes of neoliberal governance.